2 fotos van bordje op hotel aan de vooravond van Dodenherdenking. Tekst 'Deutsche nicht erwünscht' - Meerendonk, Ben van
2 fotos van bordje op hotel aan de vooravond van Dodenherdenking. Tekst 'Deutsche nicht erwünscht'.